(untitled) (Research, Society and Development, 2022)
The aim of the study was to understand how women deprived of liberty experience their health problems, what knowledge demands they generate, and how they learn to deal with them. Methodology: Qualitative study conducted in November/2019, with 18 women deprived of liberty in a women’s penitentiary in the interior of Paraíba, through focus groups. The thematic categorical content analysis was used in its three phases, to elaborate the themes that constitute the unit of meaning, such as: health problems and difficulties faced by women deprived of freedom and experiences and behaviors in prison: knowledge gaps. Results: Women deprived of liberty present health problems, many of them, acquired before incarceration, so they need information about these health problems and how to treat them inside the penitentiary. Moreover, they highlight the inadequate forms of approach to health issues, carried out in the penitentiary, where there are the difficulties encountered to access health services inside and outside the penitentiary. The women present health problems, have difficulties in understanding the information received, perceive imprecision in the attendance to allow self-care and report the difficulty of access to the health service inside and outside the penitentiary. Given the above, it is concluded that there is a need for the actions developed in prison for women to be reprogrammed in order to fill the gaps in knowledge and subsidize them in their needs, in relation to the behaviors, experiences and difficulties experienced in prison.